2011
DOI: 10.1111/j.1945-1474.2010.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Visit Cycle Time Using Patient Flow Analysis in a High–Volume Inner–City Hospital–Based Ambulatory Clinic Serving Minority New Yorkers

Abstract: Patient waiting time and waiting room congestion are quality indicators that are related to efficiency of ambulatory care systems and patient satisfaction. Our main purpose was to test a program to decrease patient visit cycle time, while maintaining high-quality healthcare in a high-volume inner-city hospital-based clinic in New York City. Use of patient flow analysis and the creation of patient care teams proved useful in identifying areas for improvement, target, and measure effectiveness of interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A hospital ambulatory clinic analysis of patient flow led to health service delivery improvement by implementing fewer patient stops, better communication among staff, regular brief meetings, and pre-assessment of patient schedules. 9 In the present study, good practices and areas for improvement were identified and could serve as the basis for recommendations for better delivery of services in UPHS.…”
Section: Discussionmentioning
confidence: 97%
“…A hospital ambulatory clinic analysis of patient flow led to health service delivery improvement by implementing fewer patient stops, better communication among staff, regular brief meetings, and pre-assessment of patient schedules. 9 In the present study, good practices and areas for improvement were identified and could serve as the basis for recommendations for better delivery of services in UPHS.…”
Section: Discussionmentioning
confidence: 97%
“…The first step was to use PFA to assess the existing workflow and establish a baseline for comparison. PFA is a broadly replicable practice by which the entire care process is outlined, from the patient perspective, to identify inefficiencies or bottlenecks and develop potential solutions [9][10][11]. The PFA involves quantifying the amount of time spent at each step, identifying which staff members are involved, and describing the specific tasks performed during each component of the visit.…”
Section: Patient Flow Analysismentioning
confidence: 99%
“…PFA is a broadly replicable practice by which the entire care process is outlined, from the patient perspective, to identify ine ciencies or bottlenecks and develop potential solutions. [9][10][11] The PFA involves quantifying the amount of time at each step, identifying which staff are involved, and describing the speci c tasks performed at each component of the visit. This data-gathering phase took place from February 2019 through May 2019 and consisted of in-person observations as well as extraction of data from the electronic medical record (EMR).…”
Section: Patient Flow Analysismentioning
confidence: 99%